Verbal Phraseological Units As A Component Member Of Proverbs - Khadjieva D.T; Ermukhanbetova F.F. (Zien Journals, 2024)
The article is an attempt in analyzing occasional verbal phraseological units in the combination of proverbs in literary texts of English and Karakalpak languages.
Keywords: Phraseological units; functions; communicative; cognitive and nominative